2020
DOI: 10.1016/j.colsurfa.2020.124914
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of surfactant-polyelectrolyte complex using valvejet 3D printing-aided colloidal self assembly

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Past 3DP studies into hydrogels have focused on agar (Serizawa, et al, 2014), starch (Huan Chen, Xie, Chen, & Zheng, 2019), alginate (Jin, Compaan, Bhattacharjee, & Huang, 2016) and mixtures of materials (Fenton, Gholamipour-Shirazi, Daffner, Mills, & Pelan, 2021;Z. Liu, Bhandari, Prakash, Mantihal, & Zhang, 2019;Vadodaria, He, Mills, & Wildman, 2020) One biopolymer of specific interest in hydrogel 3DP is kappa-carrageenan (κC). κC is an anionic, sulphated polysaccharide extracted from an edible seaweed named Rhodophyta.…”
Section: Introductionmentioning
confidence: 99%
“…Past 3DP studies into hydrogels have focused on agar (Serizawa, et al, 2014), starch (Huan Chen, Xie, Chen, & Zheng, 2019), alginate (Jin, Compaan, Bhattacharjee, & Huang, 2016) and mixtures of materials (Fenton, Gholamipour-Shirazi, Daffner, Mills, & Pelan, 2021;Z. Liu, Bhandari, Prakash, Mantihal, & Zhang, 2019;Vadodaria, He, Mills, & Wildman, 2020) One biopolymer of specific interest in hydrogel 3DP is kappa-carrageenan (κC). κC is an anionic, sulphated polysaccharide extracted from an edible seaweed named Rhodophyta.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of the propolis inclusion complexes enhanced the antibacterial and wound-healing properties of the dressings. Vadodaria et al reported the elaboration of surfactant-polyelectrolyte complexes using a valvejet 3D printer [158]. These complexes were obtained by printing alternating layers of sodium dodecyl sulfate (surfactant) and CS (polyelectrolyte).…”
Section: Incorporation Of Chitosan Micro/nanoparticles In Printing Inksmentioning
confidence: 99%
“…Three-dimensional printing and bioprinting have rapidly evolved with major applications in several fields, including biofabrication and regenerative medicine, [58][59][60][61][62] self-assembly of colloidal particles for complex formation, 58,63 simulated neural networks, 64,65 neural culture systems and the engineering of their implantation, [66][67][68][69] muscular networks, 70 vaccine and drug delivery, [71][72][73] and molecular diagnostics [74][75][76][77] (Figure 3). Three-dimensional bioprinting technology, compared to the traditional methods, holds promise as a novel gene delivery application that offers precise spatiotemporal control on DNA transfection to repair and regenerate tissues.…”
Section: Bioprinting Applicationsmentioning
confidence: 99%